Phonotactic Constraints Are Activated across Languages in Bilinguals - Freeman, Max R.; Blumenfeld, Henrike K.; Marian, Viorica (Frontiers in Psychology, 2016)
During spoken language comprehension, auditory input activates a bilingual’s two languages in parallel based on phonological representations that are shared across languages. However, it is unclear whether bilinguals access phonotactic constraints from the non-target language during target language processing. For example, in Spanish, words with s+ consonant onsets cannot exist, and phonotactic constraints call for epenthesis (addition of a vowel, e.g., stable/estable). Native Spanish speakers may produce English words such as estudy (“study”) with epenthesis, suggesting that these bilinguals apply Spanish phonotactic constraints when speaking English. The present study is the first to examine whether bilinguals access Spanish phonotactic constraints during English comprehension. In an English cross-modal priming lexical decision task, Spanish-English bilinguals and English monolinguals heard English cognate and non-cognate primes containing s+consonant onsets or controls without s+onsets, followed by a lexical decision on visual targets with the /e/ phonotactic constraint or controls without /e/. Results revealed that bilinguals were faster to respond to /es/ non-word targets preceded by s+ cognate primes and /es/ and /e/ non-word targets preceded by s+ non-cognate primes, confirming that English primes containing s+ onsets activated Spanish phonotactic constraints. These findings are discussed within current accounts of parallel activation of two languages during bilingual spoken language comprehension, which may be expanded to include activation of phonotactic constraints from the irrelevant language.